Accountability, Transparency, and Community Participation in the Management of Direct Cash Assistance (BLT) for Community Empowerment in Bantan District in 2024 - Lovita Afriani; Husnul Muttaqin (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the application of the principles of accountability, transparency, and community participation in the management of Village Fund Direct Cash Assistance (BLT-DD) in Bantan District, Bengkalis Regency in 2024, as part of the policy of accelerating the elimination of extreme poverty in accordance with Presidential Instruction Number 4 of 2022. The research method used is a qualitative approach with a case study design. Data collection was carried out through in-depth interviews and documentation, with purposive sampling techniques in eight villages with the status of Independent Villages which had more than 40 families of BLT-DD recipients. The results of the study show that the management of BLT-DD in Bantan District has been carried out in accordance with the provisions of laws and regulations, with a budget allocation of 25% of the Village Fund. The principle of accountability is realized through compliance with procedures for planning, determining, and distributing assistance, as well as active supervision by the Village Consultative Body (BPD). Transparency is implemented through information disclosure to the public, both through village deliberations, information boards, and village social media. Community participation is reflected in the involvement of residents at the stage of data collection, village deliberations, and supervision of aid distribution. However, the main obstacle is still found in the aspect of collecting recipient data due to changes in budget policies and the dynamics of socio-economic conditions of the community